Investigate the Odontogenic Differentiation and Dentin–Pulp Tissue Regeneration Potential of Neural Crest Cells - Zhang, Maolin; Zhang, Xiaochen; Luo, Jiaxin; Yan, Ran; Niibe, Kunimichi; Egusa, Hiroshi; Zhang, Zhiyuan; Xie, Ming; Jiang, Xinquan (Frontiers in Bioengineering and Biotechnology, 2020)
Stem cell-based developmental engineering has been considered as a promising strategy for tissue/organ regeneration. Tooth is formed by sequential reciprocal interactions between epithelium derived from surface ectoderm and mesenchymal cells derived from cranial neural crest. The neural crest cell is an appealing cell source for tooth development and regeneration research. In this study, we investigated the odontogenic differentiation and dentin-pulp complex regeneration potential of neural crest cells. Our results showed that neural crest cells (O9-1 mouse cranial neural crest cell line) can sequentially differentiate into dentin matrix acidic phosphoprotein 1 (Dmp-1) positive odontoblasts within a developing tooth germ in vitro. Moreover, O9-1 cells and induced pluripotent stem cells (iPSCs)-derived neural crest-like cells (iNCLCs) can form well organized vascularized dentin-pulp complex when transplanted in vivo with tooth scaffold. Furthermore, both O9-1 cells and iNCLCs can be guided differentiation into odontoblast-like cells, positive staining with odontogenic related markers Dmp-1 and dentin sialophosphoprotein (Dspp) under odontogenic induction with the administration of BMP-4. These results demonstrated that neural crest cells, especially the unlimited iNCLCs, are promising cell sources for tooth development and dental tissue/tooth organ regeneration studies.